2009
DOI: 10.1002/aic.12107
|View full text |Cite
|
Sign up to set email alerts
|

A superstructure‐based optimal synthesis of PSA cycles for post‐combustion CO2 capture

Abstract: Recent developments have shown pressure/vacuum swing adsorption (PSA/VSA) to be a promising option to effectively capture CO 2 from flue gas streams. In most commercial PSA cycles, the weakly adsorbed component in the mixture is the desired product, and enriching the strongly adsorbed CO 2 is not a concern. On the other hand, it is necessary to concentrate CO 2 to high purity to reduce CO 2 sequestration costs and minimize safety and environmental risks. Thus, it is necessary to develop PSA processes specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
119
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 40 publications
0
119
1
Order By: Relevance
“…For the selected cycle, all the step times, blowdown pressure, and flowrates of rinse and purge steps should be determined [25,[188][189][190][191][192]. Alternatively, it has been suggested that a general "super-cycle" can be used to estimate the optimal duration of each of the steps [193].…”
Section: Advances In Process Engineeringmentioning
confidence: 99%
“…For the selected cycle, all the step times, blowdown pressure, and flowrates of rinse and purge steps should be determined [25,[188][189][190][191][192]. Alternatively, it has been suggested that a general "super-cycle" can be used to estimate the optimal duration of each of the steps [193].…”
Section: Advances In Process Engineeringmentioning
confidence: 99%
“…This approach can be applied to a wide variety of sorbents, as well as feed and product specifications. We also note that a similar optimization approach was recently applied to precombustion CO 2 capture in IGCC processes, 5 where the energy requirements for PSA were only 46.8 kWh/tonne CO 2 captured, an order of magnitude less.…”
mentioning
confidence: 98%
“…For a 583 MW PC plant (Case 9 in Exhibit), the amount of CO 2 3 we agree that the energy requirements for PSA are high, and CO 2 compression costs still need to be considered. On the other hand, in our study 1 we have considered only a standard sorbent, Zeolite 13X. As we cited, a number of higher performing sorbents, such as K-promoted Hydrotalcite, are also being investigated (see, e.g.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus both the sequential and simultaneous approaches have been successfully applied to a wide range of problems, and both are in active use. Recently, for example, the optimization of periodic adsorption processes has been considered by Vetukuri et al 14 using the sequential approach and by Agarwal et al 15,16 using the simultaneous approach. Features of the two approaches can also be combined into a quasi-sequential approach.…”
mentioning
confidence: 99%